Preimplantation Genetic Diagnosis- International Standards and the Law of the Republic of Serbia - Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The process of biomedical assisted reproduction, in addition to the treatment of infertility, also can be implemented for the purpose of prevention of transmission of serious hereditary disease to offspring. This is possible thanks to the preimplantation genetic diagnosis, which involves genetic testing of a few cells of the embryo in the early stage of development before implantation in a woman's body, and its elimination in the case of determining the genetic anomaly. The process of the preimplantation genetic diagnosis faces several constitutional values ​​and raises a series of questions. Some of them were answered by European Court of Human Rights in the case  Costa and Pavan v. Italiy. The subject of the paper is the analysis of this decision, which is important from a constitutional point of view, because it establishes guidelines for the interpretation of rules of domestic law. The second task of the paper is the analysis of normative solutions of our legal system in this area, in order to test their compliance with the standards set in this Court's decision.